Inter-occurrence times and universal laws in finance, earthquakes and genomes. (July 2016) - Tsallis, Constantino
Abstract: A plethora of natural, artificial and social systems exist which do not belong to the Boltzmann–Gibbs (BG) statistical-mechanical world, based on the standard additive entropy SBG and its associated exponential BG factor. Frequent behaviors in such complex systems have been shown to be closely related to q -statistics instead, based on the nonadditive entropy Sq (with S 1 = S B G ), and its associated q -exponential factor which generalizes the usual BG one. In fact, a wide range of phenomena of quite different nature exist which can be described and, in the simplest cases, understood through analytic (and explicit) functions and probability distributions which exhibit some universal features. Universality classes are concomitantly observed which can be characterized through indices such as q . We will exhibit here some such cases, namely concerning the distribution of inter-occurrence (or inter-event) times in the areas of finance, earthquakes and genomes.